Energy performance of the infiltrate and elevation earth-sheltered buildings in the area of the city of Kragujevac – Numerical investigation - Nešović, Aleksandar (Arhitektura i urbanizam, 2023)
This paper investigated the energy potential of different modern earth-sheltered building types, during a seven-month (October 1 to May 1), to achieve sustainable development. The subject of the research is a one-story residential building (total net area 102.5 m2), intended for a family of four, located in the territory of the city of Kragujevac (central Serbia). The heating system consists of a ground source heat pump, geothermal vertical probes, floor panel heaters, and two circulation pumps. Four types of infiltrated earth-sheltered buildings, as well as one elevation earth-sheltered building, were investigated by numerical analysis (using the EnergyPlus software). The energy performances of all mentioned earth-sheltered buildings were compared with the energy performance of classic above-ground buildings. All buildings have the same geometric, construction, and thermo-technical performance. The research results showed that, in infiltrated earth-sheltered buildings, the annual consumption of final (electrical) energy can be reduced by 2.53-21.64% (depending on the number of external building elements in direct contact with the soil). Modern architecture should still be focused on the development of elevation earth-sheltered buildings because in them the annual consumption of final (electrical) energy for heating can be reduced by more than 40%.
Keywords: Earth-sheltered building; Energy efficiency; EnergyPlus; Google SketchUp; Location parameters